Implementing Eco-Learning–Based Instructional Media to Improve Students’ Learning Motivation at an Elementary School in Bunut Barat - Anim Anim; Lis Supiatman; Arifah Febriani; Amanda Puspita Ningrum; Yoanda Wasillah Mei Erwin (Ali Institute of Research and Publication, 2026)
This community service activity aims to improve students’ learning motivation through the implementation of creative eco-learning, which is a learning approach based on simple media made from recycled materials. The activity was conducted in Grade III at UPTD SD Negeri 016502 Bunut Barat, involving 32 students. The developed media included: (1) a multiplication tool made from used cardboard for Mathematics, (2) a body parts learning media made from recycled carton for English, and (3) a sentence arrangement media made from used plastic cups for Indonesian language learning. The implementation method consisted of socialization, media development, classroom trials, and evaluation. The evaluation was conducted using a learning motivation questionnaire with seven indicators: interest, activeness, confidence, cooperation, independence, interest in the media, and persistence. The results showed that the average student motivation increased from 3.06 (moderate category) to 4.44 (high category). The highest improvement was found in interest in the media, increasing from 2.9 to 4.7, and confidence from 2.8 to 4.1. The lowest increase was in cooperation, from 3.4 to 4.6. The paired sample t-test results indicated a significant difference between students’ motivation before and after the implementation of creative eco-learning, with t(31) = 74.98 and a significance value of 0.000 (< 0.05). Overall, this activity had a positive impact on students’ activeness, independence, and enthusiasm. Observations showed that student engagement increased by up to 75%, and formative test scores improved by an average of 15–20%. In addition, the activity enhanced teachers’ skills in utilizing recycled materials to create creative and environmentally friendly learning media.